Hubungan Disiplin Kerja Dan Motivasi Dalam Meningkatkan Produktivitas Kerja Karyawan PT Pandu Siwi Sentosa - Ismail Fahmi Tarigan; Akman Daulay; Windi Aginta (Fakultas Ekonomi dan Bisnis, Universitas Catur Insan Cendekia, 2021)
This study aims to determine the effect of work discipline on employee productivity at PT Pandu Siwi Sentosa Medan. To determine the relationship between work motivation and work productivity of employees at PT Pandu Siwi Sentosa Medan. This study aims to determine the relationship between discipline and work motivation with employee work productivity at PT Pandu Siwi Sentosa Medan. This type of research uses quantitative research conducted at PT. Pandu Siwi Sentosa Medan from August 2019 to January 2020. The population in this study was the total number of employees, which consisted of 50 workers. By determining the number of samples developed and using several samples with an error rate of 5%, the sample in this study amounted to 50 workers or employees. The method used is the method of observation, questionnaire method, and interview method. The results showed that the hypothesis can be accepted with a value of 4.955 so that the hypothesis is accepted. So it can be concluded that Work Discipline has a positive and significant effect on the work productivity of PT. Pandu Siwi Sentosa Medan where the t table value is 2.878 from t table 2.010 and has a significance value of 0.002 from 0.05. Motivation has a positive and significant effect on the Employee Work Productivity of PT. Pandu Siwi Sentosa Medan with a t-count value of 2.315 from t-table 2.010 and has a significance value of 0.004 from 0.05. The conclusion of this study is that work discipline and motivation have a positive and significant effect on employee productivity at PT. Pandu Siwi Sentosa Medan. Keywords: Discipline, Motivation, and Productivity